Hip-Spine Syndrome in Patients With Spinal Cord Injuries: Hyperlordosis Associated With Severe Hip Flexion Contracture - Isaac Rhee; Woo Sung Do; Kun-Bo Park; Byoung Kyu Park; Hyun Woo Kim (Frontiers Media S.A., 2021)
Aim: Spinal cord injury (SCI)-related flaccid paralysis may result in a debilitating hyperlordosis associated with a progressive hip flexion contracture. The aim of this study was to evaluate the correction of hip flexion contractures and lumbar hyperlordosis in paraplegic patients that had a history of spinal cord injuries.Methods: A retrospective review was performed on 29 hips of 15 consecutive patients who underwent corrective surgeries for severe hip flexion deformity from 2006 to 2018. The mean age at surgery was 10.1 years (2.7 to 15.8), and the mean follow-up was 68 months (7 to 143). Relevant medical, surgical, and postoperative information was collected from the medical records and radiographs.Results: Improvements were seen in the mean hip flexion contracture (p < 0.001) with 100% hip correction at surgery and 92.1% at the latest follow-up. Mean lumbar lordosis decreased (p = 0.029) while the mean Cobb angle increased (p = 0.001) at the latest follow up. Functional score subdomains of the Spinal Cord Independence Measure, Functional Independence Measure, and modified Barthel activities of daily living (ADL) scores remained the same at the final follow-up.Conclusion: For paraplegic SCI patients, we found an association between treating the hip flexion contracture and indirect correction of their lumbar hyperlordosis. We recommend the surgeon carefully examine the hip pathology when managing SCI-related spinal deformities, especially increased lumbar lordosis.